PERILAKU MENYONTEK SISWA SMA NEGERI DI KOTA PADANG SERTA UPAYA PENCEGAHAN OLEH GURU BK - Agustin, Virza (Konselor, 2013)
This research is a descriptive study attempted to describe the behavior of students systematically and prevent cheating by the guidance and counseling teacher at Public Senior High School in Padang. The instrument used was a questionnaire about cheating behaviors, background factors and prevention by the guidance and counseling teacher. From 389 students, it was found that the cheating behavior of students is high level, both in term of form or the background, while the services provided by the guidance and counseling teacher still low.Keywords: cheating behaviour; prevention poll conducted by the Guidance and Counselling